2018
DOI: 10.1029/2018ja025414
|View full text |Cite
|
Sign up to set email alerts
|

Solar Wind Induced Waves in the Skies of Mars: Ionospheric Compression, Energization, and Escape Resulting From the Impact of Ultralow Frequency Magnetosonic Waves Generated Upstream of the Martian Bow Shock

Abstract: Using data from the National Aeronautics and Space Administration Mars Atmosphere and Voltatile EvolutioN and the European Space Agency Mars Express spacecraft, we show that transient phenomena in the foreshock and solar wind can directly inject energy into the ionosphere of Mars. We demonstrate that the impact of compressive ultralow frequency waves in the solar wind on the induced magnetospheres drive compressional, linearly polarized, magnetosonic ultralow frequency waves in the ionosphere, and a localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 94 publications
7
62
0
Order By: Relevance
“…Such waves have been observed frequently in the upstream solar wind at Mars and other unmagnetized bodies such as comets, although the structures reported here are larger in amplitude and highly steepened, compared to the sinusoidal waves often seen (e.g., Brain et al, 2002;Mazelle et al, 2004;Russell et al, 1990Russell et al, , 2006Tsurutani & Smith, 1986). A recent study by Collinson et al (2018) reported foreshock structures at Mars similar to those reported here, noting that such structures were likely generated by ion-ion instabilities upstream of the Martian shock. We leave a detailed analysis and determination of these foreshock structures for a future study and simply refer to them as foreshock structures that are assumed, ignoring any wave propagation, to convect with the solar wind, for the remainder of this paper.…”
Section: Discussion and Preliminary Interpretations Of Modulated Penesupporting
confidence: 68%
See 1 more Smart Citation
“…Such waves have been observed frequently in the upstream solar wind at Mars and other unmagnetized bodies such as comets, although the structures reported here are larger in amplitude and highly steepened, compared to the sinusoidal waves often seen (e.g., Brain et al, 2002;Mazelle et al, 2004;Russell et al, 1990Russell et al, , 2006Tsurutani & Smith, 1986). A recent study by Collinson et al (2018) reported foreshock structures at Mars similar to those reported here, noting that such structures were likely generated by ion-ion instabilities upstream of the Martian shock. We leave a detailed analysis and determination of these foreshock structures for a future study and simply refer to them as foreshock structures that are assumed, ignoring any wave propagation, to convect with the solar wind, for the remainder of this paper.…”
Section: Discussion and Preliminary Interpretations Of Modulated Penesupporting
confidence: 68%
“…At first glance, the plasma characteristics of these structures, namely, the enhanced magnetic field strength, enhanced proton densities, and solar wind deflection and deceleration, suggest that these structures may be Short Large Amplitude Magnetic Structures (SLAMS), which are observed at Earth during quasi-parallel shock conditions (e.g., Giacalone et al, 1993;Lucek et al, 2004;Schwartz & Burgess, 1991;Schwartz et al, 1992). A recent study by Collinson et al (2018) reported foreshock structures at Mars similar to those reported here, noting that such structures were likely generated by ion-ion instabilities upstream of the Martian shock. Preliminary analysis shows that the time cadence of occurrence of these structures in the SWIA frame is the same as the upstream proton gyrofrequency, suggesting that these structures, if convecting past the spacecraft at the solar wind velocity, may be related to ultralow frequency waves generated further upstream, perhaps by the interaction between solar wind protons and newly ionized exospheric ions.…”
Section: Discussion and Preliminary Interpretations Of Modulated Penementioning
confidence: 99%
“…The full view of the various stages of sinusoidal wave evolution during this event on 2015 February 12 are demonstrated by the magnetic field variations in four time intervals marked by different color bars in Figure 2(a): quasi-sinusoidal low-frequency waves (QSLFWs), nonsinusoidal phase-steepened waves (NPSWs), fast mode periodic shocks (FMPSs), and magnetosonic collisionless shocks (MCSs). Individual stage of the wave evolution have been observed at Mars (Dubinin & Fraenz 2016;Collinson et al 2018;Halekas et al 2019). The interplanetary magnetic field (Figure 2(a)) is measured by the Magnetometer (MAG) instrument (Connerney et al 2015).…”
Section: Observationsmentioning
confidence: 99%
“…As the complexity and dynamic nature of the Martian magnetosphere have been revealed (DiBraccio et al, ; Halekas et al, ; Ruhunusiri et al, ), the importance of identifying and understanding each channel of energy flows carried by particles and fields in the near Mars space has become increasingly recognized. For instance, recent observations showed that narrow band ultralow frequency (ULF) waves generated upstream of the bow shock propagate all the way through the magnetosheath down to the dayside upper ionosphere, wherein wave‐particle interaction causes significant heating of ionospheric heavy ions (Collinson et al, ; Fowler et al, , ). These waves of upstream origin typically oscillate near the upstream proton cyclotron frequency ( f cp(upstream) ) with left‐handed polarizations in the spacecraft frame (which approximately corresponds to the Mars rest frame), and they are interpreted as intrinsically right‐handed waves propagating upstream in the solar wind frame, presumably resonating with newborn pickup protons or reflected solar wind protons (Romanelli et al, ; Ruhunusiri et al, ).…”
Section: Introductionmentioning
confidence: 99%